2021
DOI: 10.1038/s41467-021-26982-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping protein carboxymethylation sites provides insights into their role in proteostasis and cell proliferation

Abstract: Posttranslational mechanisms play a key role in modifying the abundance and function of cellular proteins. Among these, modification by advanced glycation end products has been shown to accumulate during aging and age-associated diseases but specific protein targets and functional consequences remain largely unexplored. Here, we devise a proteomic strategy to identify sites of carboxymethyllysine modification, one of the most abundant advanced glycation end products. We identify over 1000 sites of protein carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…Only interactions with an interaction score greater than 0.95 were included and any disconnected nodes were removed. Remaining STRING network was exported to Cytoscape [ 20 ]. Cluster labels were assigned based on the KEGG analyses of pathways that were associated with the greatest number of proteins in that cluster.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only interactions with an interaction score greater than 0.95 were included and any disconnected nodes were removed. Remaining STRING network was exported to Cytoscape [ 20 ]. Cluster labels were assigned based on the KEGG analyses of pathways that were associated with the greatest number of proteins in that cluster.…”
Section: Methodsmentioning
confidence: 99%
“… Protein–protein interaction network of MGO-modified proteins generated using STRING database v11.5 and Cytoscape v3.9.0 [ 19 , 20 ]. Size of the node (protein) reflects the number of MGO modifications found on that protein (ranging from 1–7).…”
Section: Figurementioning
confidence: 99%
“…Since advanced glycation end products accumulate during aging and age-associated diseases, a recent study demonstrated, by using quantitative proteomics, that protein glycation triggers a proteotoxic response and indirectly affects the protein degradation machinery regulating the cellular function compromised during aging [107]. An interesting article demonstrated that FOXO (forkhead box, class O) transcription factors regulate metabolic homeostasis as well as longevity using Drosophila transgenic lines expressing high and relatively low foxo levels and overexpressed foxo, either ubiquitously or in a tissue-specific manner [108].…”
Section: Proteostasismentioning
confidence: 99%
“…As the essential components of living organisms, [1] proteins play important roles in the function including catalytic reactions, [2] signal transduction, [3] recognition sensing, [4] and so on. Their spatiotemporal distribution, structural function, dynamic changes and interaction mode of these proteins could determine the normal physiological activity of cells, including proliferation, differentiation, apoptosis, et al [5–11] . The abnormity of proteins will induce the occurrence and development of diseases [12] .…”
Section: Introductionmentioning
confidence: 99%
“…As the essential components of living organisms, [1] proteins play important roles in the function including catalytic reactions, [2] signal transduction, [3] recognition sensing, [4] and so on. Their spatiotemporal distribution, structural function, dynamic changes and interaction mode of these proteins could determine the normal physiological activity of cells, including proliferation, differentiation, apoptosis, et al [5][6][7][8][9][10][11] The abnormity of proteins will induce the occurrence and development of diseases. [12] Therefore, the analysis and regulation of proteins are of great significance for studying the biological functions of proteins, explaining the mechanism of biological signal transduction, and developing new disease diagnosis and treatment methods.…”
Section: Introductionmentioning
confidence: 99%